Diagnostic precision, safety, and patient experience of the freehand transperineal prostate biopsy technique under local anesthesia – A single-center experience - Aikaterini Eleftheriadou; Charlotte Collins; Dilaaniy Kannapiran; Faria Antara; Moustafa Elhammadi; Sarosh Janardanan; Michael Mikail; Nimalan Arumainayagam; Danny Darlington Carbin (Indian Journal of Urology)
Introduction: Transperineal access systems are commonly used to stabilize the biopsy needle with the ultrasound probe in local anesthetic transperineal biopsies (LATPs). However, these devices are expensive and nonreusable and restrict the access to some of the prostatic zones causing excessive probe movement and procedural pain. We aim to assess the pain tolerability, diagnostic value, and safety of the totally freehand LATP (tF-LATP) technique. Methods: Patients undergoing tF-LATP for suspected prostate cancer (PCa) from February 2024 to June 2024 were prospectively included. Data on the prostate-specific antigen (PSA) levels, prostate size, prostate multiparametric magnetic resonance imaging findings, cancer detection, need for immediate rebiopsy due to undersampling (with predefined criteria for immediate rebiopsy), tolerability, and complications were collected. Pain levels were assessed using the Visual Analog Scale (VAS) scores (scores 1–10) at rectal probe insertion and immediately postbiopsy. Results: Seventy-five patients (n = 75) underwent tF-LATP, with a median age of 67 years. The median PSA level was 7.05 ng/mL, and the median prostate size was 55 cc. During the procedure, the VAS ranged from 1 to 4 (median: 2). Postprocedure the VAS scores ranged from 1 to 2 (median: 1). Forty-four patients (59%) tested positive for PCa. There were no instances of urinary retention, sepsis, or hematuria requiring admission, and none required immediate rebiopsy due to undersampling as per the predefined rebiopsy criteria. Conclusions: The tF-LATP technique demonstrateed excellent safety, diagnostic efficacy, and satisfactory tolerability. With its cost-effectiveness and enhanced accessibility to all the prostatic lobes, clinicians are encouraged to integrate this technique more widely into clinical practice to maximize its advantages.